2013
DOI: 10.7171/jbt.13-2403-002
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Whole-Body Zebrafish Sectioning Methods for Mass Spectrometry Imaging

Abstract: Mass spectrometry imaging (MSI) methods and protocols have become widely adapted to a variety of tissues and species. However, the MSI literature contains minimal information on whole-body cryosection preparation for the zebrafish (ZF; Danio rerio), a model organism routinely used in developmental, toxicity, and carcinogenicity studies. The optimal medium for embedding and cryosectioning a whole organism or soft-tissue specimen for histological examination is a synthetic polymer mixture that is incompatible wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 19 publications
2
63
0
Order By: Relevance
“…This was the only medium that was not too hard to tear the section, disintegrating the tissues and hindering the histological analysis, but hard enough to maintain rigidity at a proper temperature. The solution was also the most pliable and stable medium for frog cross‐sectioning, in agreement with similar results found for zebrafish cryosectioning 28 . The minimum section thickness we achieved was 15 μm.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This was the only medium that was not too hard to tear the section, disintegrating the tissues and hindering the histological analysis, but hard enough to maintain rigidity at a proper temperature. The solution was also the most pliable and stable medium for frog cross‐sectioning, in agreement with similar results found for zebrafish cryosectioning 28 . The minimum section thickness we achieved was 15 μm.…”
Section: Resultssupporting
confidence: 89%
“…We tested three different embedding media: 2% carboxymethyl cellulose (CMC), 5% CMC, and 5% CMC + 10% gelatin based on procedures described for zebrafish by Nelson et al 28 and Perez et al 29 We removed the arms and legs of the frogs 7 , placed the whole body in a flexible, peel‐away mold with embedding media, and oriented it to sagittal sectioning. To visualize simultaneously as many internal organs as possible, we analyzed three regions of the body through mid‐sagittal, left, and right parasagittal sections.…”
Section: Methodsmentioning
confidence: 99%
“…Slices were taken at this thickness due to the ease of reproducibility with the chosen embedding medium. A selection of embedding media has previously been studied by Nelson et al . for the purpose of freezing and cryosectioning zebra fish.…”
Section: Resultsmentioning
confidence: 99%
“…Slices were taken at this thickness due to the ease of reproducibility with the chosen embedding medium. A selection of embedding media has previously been studied by Nelson et al [21] for the purpose of freezing and cryosectioning zebra fish. They determined that a more optimal medium consisting of 5% CMC and 10% gelatine mixture can be used to achieve reproducible slices of 16 μm thickness.…”
Section: Resultsmentioning
confidence: 99%
“…Lagarrigue et al dipped the slides in ice‐cold 10 mM AmP after matrix application for suppressing α‐CHCA matrix cluster formation . In the same concept, Nelson et al investigated matrix application conditions specifically for peptide and protein detection in whole‐body zebrafish by MALDI MSI . The writers showed for the first time AmP (6 mM AmP in 5 mg/mL α‐CHCA) usage with an automatic sprayer and reported that AmP in MALDI matrix enhanced analyte intensities.…”
Section: Discussionmentioning
confidence: 99%